SOEKARNO AND JAVANESE SOVEREIGNTY CONCEPT CASE STUDY: GUIDED DEMOCRACY ERA - Elisabeth Ermuliana Kembaren Kembaren (Prodi Ilmu Politik, 2021)
This research discusses the influence of the Javanese sovereignty concept in the practices of Soekarnoâ€™s regime under the Guided Democracy era (1959-1965). Guided democracy has corrupted the separation of powers in trias politica. The research is a qualitative research designed with a historical, descriptive approach that using literature study. The theory employed based on the javanese sovereignty concept, where kings are the centers of the sovereignty. The research finds that the centralization of power in Soekarnoâ€™s regime under the Guided Democracy era reflects the implementation of the Javanese sovereignty concepts as adopted by the kings in the past. The practices that reflect Javanese sovereignty concept in such as the abandonments of the trias politica, Nasakom, as well as the so-called â€œlighthouseâ€ projects and the application of symbolization of power.